Answer :

Put,

Now,

Now, for

Let,

…(1)

Consider a right angle triangle ABC, with right angle at A, as shown,

Let angle = Angle ABC

AB = base,

AC = opposite,

BC =hypotenuse

We know that,

From (1)

…(2)

Also, in a right angle triangle using, Pythogoras theorem,

(hypotenuse)^{2} = (opposite)^{2} + (base)^{2}

⇒ (BC)^{2} = (AC)^{2} + (AB)^{2}

From (2),

⇒(BC)^{2} = 8AB^{2}+AB^{2}

⇒(BC)^{2} = 9AB^{2}

⇒ BC = 3AB …(3)

Now,

From (3),

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Find the principaRD Sharma - Volume 1

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar